Outcome of Dorsal Onlay Urethroplasty for Long Segment Anterior Urethral Stricture: Experience of 31 Cases - Asad, Hafiz Al; Saha, Prodyut Kumar; Hossain, AKM Shahadat; Islam, Md Waliul; Bhuiyan, Akm Musa (Bangladesh Journal of Urology, 2020)
Objective: To determine the short-term outcome of dorsolateral onlay urethroplasty in the treatment of long segment anterior urethral stricture. Materials and Methods: A prospective study from May 2011 to September 2012 is carried out in department of Urology, National Institute of Kidney Diseases and Urology, Sher-EBanglanagar, Dhaka. Thirty one patients with long anterior urethral stricture were treated by a dorsolateral onlay buccal mucosa graft. After voiding trial, they were followed up at 3 weeks and 3 months with history, physical examination, uroflowmetry and retrograde urethrogram (RGU) if required (uroflowmetry <15 ml/sec). Patients were further followedup at 3 months interval with uroflowmetry and retrograde urethrogram (RGU) if required (uroflowmetry <15 ml/sec). Successful outcome was defined as normal voiding with no surgical intervention after catheter removal. Results: Mean stricture length was 42.49±12.77 mm (range 24-70 mm) and mean follow up was 8 months (range 6 to 12 months). Three patients were found to develop stricture at anastomotic site, during follow-up and required optical internal urethrotomy and was considered as failure. One patient developed wound infection which resolved after regular dressing. Success rate was 90.32%. Conclusion: Dorsolateral onlay BMG urethroplasty is feasible for long anterior urethral stricture with good short term surgical outcome. Bangladesh Journal of Urology, Vol. 19, No. 1, Jan 2016 p.28-31